Studi Islam: Konsepsi, Kemunculan Polemik-Ideologis dan Filsafat Ilmu Pengembangannya - Alim Roswantoro (UIN Sunan Kalijaga Yogyakarta, 2016)
Islamic studies have developed from its birth time of the early Islam to nowadays time. Unfortunately, the phenomena of ideological polemics of epistemological groups of Islamic thought can still be strongly found in today’s moslim’s life. The polemics, of course, limit the human freedom of thought in order to progressively develop the Islamic knowledge. The article intends to study causes of the emergence of ideological polemics and conflicts of Islamic epistemological groups. And then it tries to give the philosophical way to make the Islamic studies continuously in the progress. The writing uses the analysis method of philosophy of science to answer the problems. The writing found that the causes of the ideological polemics are the political dominance, the idolization, and truth claim of Islamic thought or the product of Islamic studies, and to have the progressiveness of Islamic studies, the only way is to change the logic of dominance, idolization, and truth claim become that of mutually discursive communication.[Studi Islam telah berkembang dari awal kelahirannya di masa awal Islam sampai dewasa ini. Sayangnya, fenomena polemik ideologis antar kelompok-kelompok epistemologis keislaman masih secara kuat bisa ditemukan. Polemik ini tentu saja menghambat kebebasan berpikir dalam pengembangan pengetahuan keislaman. Tulisan ini bermaksud mengkaji sebab-sebab kemunculan polemik dan konflik ideologis dalam pemikiran keislaman tersebut, dan mencoba menawarkan pemecahan filosofisnya untuk mendorong studi Islam selalu berada dalam kemajuan. Tulisan ini menggunakan metode analisis filsafat ilmu untuk menganalisa maksud penelitian ini. Tulisan ini menemukan bahwa sebab kemunculan polemik ideologis antar kelompok-kelompok epistemologis keislaman adalah dominasi politik, sakralisasi, dan klaim kebenaran terhadap pemikiran keislaman, dan untuk mendapatkan progresivitas studi-studi Islam, satu-satunya cara adalah mengubah logika dominasi, sakralisasi, dan klaim kebenaran dengan nalar saling berkomunikasi dan nalar diskursif.]